Adverse effects of spinal anaesthesia for caesarean section - Vidya Rani; Doshi, Nilesh Ramanlal; Rajneesh Kumar; Upadhye, Aditi J.; Jayshree J. Upadhye (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Obstetric anaesthetists while providing anaesthesia for caesarean sections, provide care for both the mother and the unborn baby. This study was performed to evaluate the adverse effects of spinal anaesthesia for Caesarean section. Methods: The present study is a prospective observational study carried out on 100 full-term, low risk pregnant patients who had caesarean section under spinal anaesthesia at Varun Arjun medical college, Shahjahanpur, U. P., India from January 2022 to December 2022. Results: In our study, 43 (43%) patients were between 26-30 years, 32 (32%) patients were between 31-35 years, 16 (16%) patients were between 36-40 years. The 62 (62%) patients were primigravida while 38 (38%) patients were multigravida. The 66 (66%) patients were delivered by emergency caesarean section while 34 (34%) were delivered by emergency caesarean section. In our study, adverse anaesthetic effects were less. 12 (12%) patients had spinal hypotension, 11 (11%) patients had spinal headache, 10 (10%) patients had pruritus, 9 (9%) patients had shivering, 5 (5%) patients had nausea and vomiting, 4 (4%) patients had less visceral pain and neonatal Apgar score each, 3 (3%) patients had failed regional anaesthesia, 3 (3%) patients had bradycardia while 2 (2%) patients had high spinal anaesthesia, 10 (10%) patients had visceral pain. Conclusions: In our study, combination of bupivacaine and a low dose of fentanyl (0.25 μg/kg) provided excellent surgical anaesthesia with short-lasting postoperative analgesia. There were very few adverse side effects.